The transition of Samsung Electronics through its M&A with Harman International - Jung hyun Kim; Monica Young-Shin Chun; Duong Thi Hong Nhung; Jeonghwan Lee (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
The automobile industry is experiencing unprecedented change. Despite its century-old history based mostly in the art of mechanics, increased development of technology and heightened awareness of environmental issues has pushed traditional automobile manufacturers to completely re-examine their strategies. It has also newly invited nontraditional players such as electronic and IT tycoons namely, Samsung, Google, and Apple into the game. The advent of electric cars with cutting edge technology requires active participation and collaboration from diverse industries requiring cross-over joint ventures and M&As. In this light, the recent acquisition of Harman Incorporated for eight billion dollars by Samsung Electronics in 2016 is a significant event that signals great change. As the electronics tycoon expands its boundaries preparing to become an important player in the automobile industry, this study examines how Samsung increases and integrates its knowledge base and innovation capability through the M&A deal with Harman in attempts to enhance its competitiveness in the rapidly evolving automotive market.
Keywords: 650; automobile industry; autonomous driving; electric cars; M&A; open innovation; post-merger integration